In vitro release and in vivo growth-promoting effects of coated cysteamine in broilers - Youyou Liu; Biyue Zhao; Yujing Feng; Hu Zhang; Qianyun Zhang; Jia Hou; Yuming Wang; Renna Sa; Feng Zhao; Jingjing Xie (Poultry Science, 2023)
ABSTRACT: The purpose of this study was to investigate the effects of coating technology on the cysteamine (CSH) release in the digestive tract and the growth-promoting effect of enteric-coating CSH in broilers. First, using the self-developed computer-controlled simulated digestion system to mimic the digestion process in vitro, the release of 2 coated CSH (CSH-I and CSH-Ⅱ) were studied. The results showed that less than 10% of CSH-I was released after gastric digestion and 52.35% of CSH-I was released with additional 4 h of small intestinal digestion. In contrast, 83.62% of CSH-Ⅱ was released during the gastric digestion. In order to verify the growth-promoting effects of CSH-I, a feeding trial was conducted in a completely randomized block arrangement with 3 treatments in 6 blocks, 5 chickens per replicate. Broilers were fed with corn-soybean meal diet either supplemented with 0 (CON), 200 mg/kg uncoated CSH (CSH) or 200 mg/kg CSH-I from d 7 to 42, respectively. Body weight and FI was recorded at d 21 and 42. Excreta were collected from d 39 to d 42 to determine the total tract retention (TTR) of dietary nutrients. In comparisons with controls, birds fed with CSH-I had greater BW, ADG, and ADFI and increased TTR of DM, gross energy (GE), NDF and hemicellulose (P < 0.05). In addition, duodenal villi height and surface area were also greater in those CSH-I-fed birds. In contrast, the growth performance of birds fed with uncoated CSH did not significantly differ from controls. Although the TTR of DM and GE was higher in birds fed with CSH than controls, no differences in small intestine morphology were noted. Thus, the type I coating (CSH-I) could be good enteric-coating technology to increase CSH release in the duodenum, improve digestion and duodenal morphology, and therefore growth performance in broilers.